Wh-question formation in South African sign language: a case study - De Barros, Courtney Leigh (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This thesis is a case study investigating wh-question formation in South African Sign Language (SASL). It provides the first descriptive and syntactic analysis of wh-question formation in this language, based on a collected sample. The evidence gathered for this study shows that SASL makes use of non-manual features to mark wh-question formation and possesses a full question word paradigm including WHAT, WHERE, WHEN, WHO and HOW. In the methodology, I critically engage with two issues: informant selection and data elicitation. These can greatly impact data validity "“ specifically with respect to sign language research. Ultimately, I adopt a novel, multi-layered data collection approach to ensure a valid sample. The data reveals SASL's almost exclusive placement of wh-question words in the right periphery. The absence of moved sentence-initial wh-elements in SASL poses problems for syntactic analysis using only leftward movement. It seems typologically unusual that a language predominantly selecting the right periphery as a position for wh-words would allow a complex syntactic derivation involving some null wh-element in a leftward Spec, CP and then allow for another 'copy' to appear in the right periphery. On the other hand, having Spec, CP on the right allows for far less complex derivations of wh-movement. In SASL, as in spoken language, the wh-word moves to Spec, CP to check the [WH] feature in C. The difference is that this movement is rightward. Further support for a rightward analysis comes from SASL's distribution of non-manual features, and its hierarchy of negative elements and adverbials. This research represents a first step towards filling a gap in the SASL literature concerning wh-question formation, as well as a contribution to the growing body of research surrounding sign languages. Furthermore, at a higher level, this study evaluates current linguistic theory on sign languages, challenging the current cross-linguistic generalisation that wh-movement is leftward.
Keywords: South African sign language; South African sign language -- Syntax; Sign language -- Grammar